Highly efficient side-pumped solar laser with enhanced tracking-error compensation capacity - Tibúrcio, Bruno D. (2022)
We report here a significant numerical improvement in side-pumped solar laser collection efficiency and solar-to-laser conversion efficiency, with an enhanced tracking error compensation capacity. Two side-pumped configurations, a single-rod and a dual-rod scheme were studied. The former pumped a thick laser rod with the full collection area of a parabolic mirror and the latter pumped two thin laser rods simultaneously, each rod being pumped by half of the collection area of the same concentrator. Both configurations were composed of a fused silica aspheric lens and a 2D-shaped-semicylindrical pump cavity, within which the Nd:YAG rods were mounted, allowing a tight focusing of the concentrated solar pump power from the focal spot of the heliostat–parabolic mirror solar energy collection and concentration system and an efficient pumping to the laser crystals. 42.70 W continuous-wave multimode solar laser power, corresponding to 27.37 W/m2 collection efficiency, and 3.26% solar-to-laser power conversion efficiency were numerically calculated for the single-rod scheme, being 1.55 and 1.34 times, respectively, higher than the previous state-of-the-art experimental records of side-pumped solar laser. For the dual-rod scheme, 37.72 W multimode solar laser power, corresponding to 24.18 W/m2 collection efficiency, and 2.88% solar-to-laser power conversion efficiency were numerically obtained, being 1.37 and 1.19 times, respectively, more than the previous record in side-pumping configurations. More importantly, largely enhanced brightness figure of merit, thermal performance and tracking error compensation capacity were attained by the dual-rod scheme, as compared to that of the single-rod scheme.